2020
DOI: 10.1002/pds.5136
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a drug safety communication on the severity of benzonatate exposures reported to poison centers

Abstract: Purpose Identify if publication of the 2010 drug safety communication (DSC) regarding benzonatate was associated with a decrease in the incidence of severe benzonatate poisonings reported to United States poison centers. Methods This retrospective database study utilized the National Poison Data System to compare the incidence of severe benzonatate poisonings before and after the publication of a drug safety communication. We utilized interrupted time series analysis to compare 2000‐2010 (pre‐DSC) to 2012‐2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In this situation, NPDS may be more sensitive than claims data for looking at clinical outcomes of interest. Because specially trained CSPIs code each case with a product-specific substance code and capture detailed exposure information whenever possible, 11,24 specific dose categories for each drug were available. NPDS also captures drug exposures resulting from a family member's prescription.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this situation, NPDS may be more sensitive than claims data for looking at clinical outcomes of interest. Because specially trained CSPIs code each case with a product-specific substance code and capture detailed exposure information whenever possible, 11,24 specific dose categories for each drug were available. NPDS also captures drug exposures resulting from a family member's prescription.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Few studies reported the dosage information using the NPDS data. 24,25 Some drugs/products may have had a higher missing rate of dose information than other products. Another limitation is using national drug utilization as denominators for children, assuming who experience side effects that in NPDS are the patients for whom the medication was prescribed.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Although we included all fatalities, we did not include any "major" outcome cases as the limited information from just the coded data may not be as useful and studies utilizing coded data have already been performed. 2,24 This exclusion of major or moderate cases biases the outcomes toward fatality. There is a risk of duplicating cases from the published literature and the NPDS fatality module.…”
Section: S47mentioning
confidence: 99%
“…1 Calls to poison centers about benzonatate exposures have risen drastically (doubling since the 2012 FDA warning) with a concomitant increase in the number of severe poisonings from approximately 120 in 2012 to 240 in 2019. 2 Sporadic cases of severe benzonatate poisoning are reported in the literature. [3][4][5] This was a descriptive study using the National Poison Data System (NPDS) fatalities module in combination with a systematic review to describe the S40 Human and Experimental Toxicology 40(12S) course of severe poisoning and deaths from benzonatate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation